Teacher Talk and Student Talk: Classroom Interaction in Online CFL Class - Fatmawati, Fatmawati; Pebriani, Wastri; Marsuki, Ria Riski (Universitas Negeri Semarang, 2024)
This study explores the interaction between “Teacher Talk” and “Student Talk” in an online Chinese as a Foreign Language (CFL) class. The goal is identifying methods to leverage these dynamics to create more effective and engaging online learning environments. This research uses a qualitative research design to understand the dynamics of interactions between teachers and students in CFL online classes. Data was collected through observation and video recording in four CFL online classes with the participation of 16 students and four teachers. Data analysis uses Flanders Interaction Analysis Categories (FIAC) to identify interaction patterns and themes. The study findings show that effective interactions between teachers and students are critical in establishing collaborative and valuable online learning experiences. Effective student participation often depends on guidance and encouragement from teachers, who create a supportive and participatory learning environment.